Caste Microaggression: A Barrier to Lower Affective Filter and to Promote Inclusivityin the Classroom - Chaulagain, Sangam (International Research Journal of MMC, 2021)
This article explores the impact of caste microaggressions in classroom activitiesin the countries like Nepal. It focuses on the study of how caste microaggressions are barriers to lower affective filter and promote inclusivity in the classroom. This is a review article based on qualitative research in which the ideas are derived from different secondary sources and are arranged to support how lower-caste students are the victim of caste microaggressions in Nepali society. This article shows that the students of lower-caste families, especially the Dalits, are greatly victimized by discriminatory activities in the schools of rural areas of Nepal. To promote inclusivity and to encourage lower-caste children in learning activities, it is essential to avoid caste microaggression and to emotionally engage such students in classroom activities that have to be initiated by the teachers primarily.